FOREIGN EXPERIENCES IN THE DEVELOPMENT OF AUDIENTIFICAL MARKETS IN UZBEKISTAN - Sobitovich, Mukhamedov Umarkhon; Shavkatovich, Salaydinov Bakhtiyor; Abdulhakovna, Zakirova Sayyora; Gulomovna, Zunnunova Umida (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates foreign experiences in the development of audientifical markets in Uzbekistan. On this case, foreign experience of audio and audientifical markets in Uzbekistan has been discussed as the whole. In conclusion, comparisons of the foreign experience and Uzbek conditions were illustrated and vivid results were stated.